Mapping Student Character Education on Biotechnology Material - Radeswandri; Vebrianto, Rian; Wahyuni, Sri (Indonesian Values and Character Education Journal, 2023)
Student character education is very important in facing the challenges of the 21st century. This research aims to determine the level of student character education. Therefore, this research aims to analyze student character education in ninth-grade students. The methodology in this research uses a survey method involving 75 students who were taken at random (randomly). The instrument used was character education questions distributed via Google Forms. The data obtained was analyzed using the Statistical Program for Social Science (SPSS) application. Based on the survey results, it is known that the number of subjects consisted of 43 women and 32 men. and consisted of 4 tribes, namely Malay, Minang, Batak, and Javanese. Based on the survey results, it is also known that the average student's character education ability is in a good category with a score of 7.4, which can be explained in detail in 4 constructs, namely religious, honest, disciplined, creative, democratic, curious, caring for the environment, social caring and responsibility. In conclusion, the construct with the highest average value is environmental care and responsibility and originality with the same average value, namely 8.0, and the lowest is democracy and creativity, namely 7.2. The recommendation from this research is that the development of student character education still needs to be improved, and teachers can use the instruments used.